Attributional style in Borderline personality disorder is associated with self-esteem and loneliness - Schulze, Anna; Rommelfanger, Berit; Schendel, Elisabeth; Schott, Hannah; Lerchl, Aimee; Vonderlin, Ruben; Lis, Stefanie (Borderline Personality Disorder and Emotion Dysregulation, 2024)
Attributions are the processes by which individuals explain the causes of positive and negative events. A maladaptive attributional style has been associated with reduced self-esteem, psychosocial functioning, and mental health. Although many psychosocial interventions target an individual’s attributional style in mental disorders, studies of its alterations in Borderline Personality Disorder (BPD) are sparse. This study aimed to investigate the attributional style in patients with BPD in comparison to healthy control individuals (HC) and its association with self-esteem and psychosocial functioning. The participants (32 patients with a diagnosis of BPD, 32 HC, groups were balanced for sex, age and education) assessed their attributional style in regard to locus of control, stability and globality for positive and negative scenarios. Attributional style was compared between groups and linked to self-reports of self-esteem, loneliness and psychosocial functioning in different social domains while controlling for BPD and depressive symptom severity. Individuals diagnosed with BPD reported a maladaptive attributional style for both positive and negative events. This was found to be strongly related with lower self-esteem and higher levels of loneliness, but not with psychosocial dysfunctions assessed in different social domains. The severity of BPD and depressive symptoms did not fully explain the association of attributional style with self-esteem and loneliness. In contrast, correcting for acute psychopathology actually strengthened the relationship between self-esteem and maladaptive inferring causality for positive events. The differential association of attributional style for positive and negative events with self-esteem and psychosocial functioning highlights the importance of considering the different facets of inferring causality during psychosocial interventions. Our findings suggest that the significance of cognitive alterations may change with remission of acute BPD and depressive psychopathology, depending on the valence of an event.
Gesehen am 04.03.2025